Novel inhibitory function of miR‐125b in melanogenesis. (7th November 2013) - Kim, Kyu‐Han; Bin, Bum‐Ho; Kim, Juewon; Dong, Son Eui; Park, Phil June; Choi, Hyunjung; Kim, Beom Joon; Yu, Seok Jong; Kang, Hyojin; Kang, Hak Hee; Cho, Eun‐Gyung; Lee, Tae Ryong
Summary MicroRNAs are known to be the important regulators of skin physiology and considered as new therapeutic targets to treat skin diseases. In this study, miR‐125b was identified as a potent regulator of steady‐state melanogenesis. We found that the expression of miR‐125b was inversely related to pigment levels. A miR‐125b mimic decreased the expression of pigmentation‐related gene and melanin content, implying that miR‐125b functions to decrease pigmentation. Moreover, we observed that the reduction in miR‐125b expression in pigmented cells was at least partially due to the hypermethylation of the MIR125B‐1 promoter, and miR‐125b expression was regulated by intracellular cAMP levels.